Cyanobacterial akinete induction and its application as biofertilizer for rice cultivation - Sasidhorn Innok (2018)
Nostoc sp. VICCR1-1 was induced in order to form akinetes on the basis of nutrient modification. Phosphorus and iron were found to be the critical for akinete differentiation, especially when both elements were omitted. The number of akinete cells increased up to 20% when compared with culturing in BG110medium (without N source). In addition, CaCl2played a role in heterocyst differentiation, and was able to induce heterocyst ranging between 30% and 46%. In order to prepare akinetes as inoculum, the dried form of akinetes was prepared by mixing it with montmorillonite clay. The inoculum with the amount of 2.8 × 106cells m-2was applied to rice (Oryza sativa) fields. After harvesting, the grain yields from chemical N fertilizer, vegetative cells, and akinete inoculum treatments were not significantly different. To monitor the persistence of Nostoc sp. VICCR1-1 after harvesting, the most probable number-denaturing gradient gel electrophoresis technique using 16S rRNA gene was employed. The results indicated that the remaining population is at 2.5 × 105and 1.62 × 106cells m-2in treatments supplied with vegetative cells and akinete inocula, respectively. Akinete induction might be one of the appropriate approaches for producing cyanobacterial inoculum. © Springer Science + Business Media B.V. 2009.